2022
DOI: 10.3389/fmicb.2022.817661
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Molecular Diagnosis of Extra-Pulmonary Tuberculosis by Xpert/RIF Ultra

Abstract: Rapid detection of Mycobacterium tuberculosis complex and determination of drug resistance are essential for early diagnosis and treatment of tuberculosis (TB). Xpert MTB/RIF Ultra (Xpert Ultra), a molecular test that can simultaneously identify M. tuberculosis complex and resistance to rifampicin directly on clinical samples, is currently used. Xpert Ultra represents a helpful tool for rapid pulmonary TB diagnosis, especially in patients with paucibacillary infection. The aim of this review is to provide an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…A recent review of the diagnosis of extrapulmonary TB with the GeneXpert assay found a sensitivity of 60%–100%, depending on specimen type, and a specificity of 87.5%–100% for bone and joint specimens. 10 We did not diagnose TB in our patient until 5 years after symptom onset, by which time he had considerable destruction of the knee joint. Despite the presence of joint destruction, TB arthritis typically responds well to medical therapy and is usually treated for 6–12 months.…”
Section: Discussionmentioning
confidence: 67%
“…A recent review of the diagnosis of extrapulmonary TB with the GeneXpert assay found a sensitivity of 60%–100%, depending on specimen type, and a specificity of 87.5%–100% for bone and joint specimens. 10 We did not diagnose TB in our patient until 5 years after symptom onset, by which time he had considerable destruction of the knee joint. Despite the presence of joint destruction, TB arthritis typically responds well to medical therapy and is usually treated for 6–12 months.…”
Section: Discussionmentioning
confidence: 67%
“…A review article has compiled many previous studies on the performance of Xpert Ultra using culture and CRS as the gold standard and has reported highly varied sensitivities as 50%–84% and 37%–61% in pleural fluid, 50%–100% and 27%–70% in lymph node tissue/aspirates, 71%–96% and 33%–95% in CSF samples, and 100% and 18%–34% in urine samples, respectively. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Le test de dépistage automatisé à base de cartouche GeneXpert MTB/RIF, tout comme le test de nouvelle génération GeneXpert MTB/RIF Ultra, est le test de dépistage fondé sur un test d’amplification de l’acide nucléique le plus étudié et le plus largement accessible, en plus d’être recommandé par l’Organisation mondiale de la santé. Une récente revue des diagnostics de TB extrapulmonaire posés à l’aide du test de dépistage GeneXpert a observé une sensibilité de 60 %–100 %, selon le type d’échantillons, et une spécificité de 87,5 %–100 % pour les échantillons osseux et articulaires 10 . Dans le cas de notre patient, nous n’avons pas été en mesure de diagnostiquer une TB avant 5 ans après l’apparition des symptômes, auquel moment l’articulation de son genou avait subi une destruction considérable.…”
Section: Discussionunclassified